Respiratory Outcomes in Preterm Infants : From Infancy through Adulthood - Hibbs, Anna Maria; Muhlebach, Marianne S. (Springer International Publishing : Imprint: Humana Press, 2017)
This book presents pulmonary outcomes of prematurity, from their emergence in infancy through to their consequences in adulthood. With an increasing number of preterm births and more infants surviving, there is now a larger population of adults with lung disease originating in infancy requiring specialized care. Looking at the whole group of preterm infants, not just those with bronchopulmonary dysplasia, this text covers a wide spectrum of pulmonary outcomes, including: pulmonary hypertension, wheezing, and alterations in sleep. The chapter authors focus on critically appraising what is and is not known about each outcome and suggest key questions that still need to be answered. Respiratory Outcomes in Preterm Infants: Sequelae from Infancy through Adulthood is an ideal reference for the multidisciplinary group that cares for these preterm infants and the adults they become, including: neonatologists, pediatric pulmonologists, pediatricians, adult pulmonologists, primary care physicians, nurses, and fellows.
Keywords: Medicine.; Critical care medicine.; Respiratory organs -- Diseases.; Pediatrics.; elektronické knihy; electronic books